Comlete lactational performance of cows fed wet corn gluten feed and pellet consisting of raw soybean hulls and corn steep liquor - Ferdinand, E.E.; Titgemeyer, Evan C.; DeFrain, J.M.; Park, A.F.; Johnson, D.E.; Ethington, R.T.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated the effect of wet corn gluten feed and a novel product containing raw soybean hulls and corn steep liquor on performance in lactating dairy cows. Forty-six multiparous Holstein cows were used in a randomized incomplete block design. Cows were housed in tie stalls for the first 13 weeks of lactation and moved to group pens for the remainder of the study. Cows were blocked by calving date and assigned to control, wet corn gluten feed (20% of diet DM), or the novel product (20% of diet DM). Diets were administered as total mixed rations at the first feeding postpartum. Control contained (DM basis) 30% alfalfa hay, 15% corn silage, 32% corn, 9.3% whole cottonseed, 4.4% solvent soybean meal (SBM), 3.3% expeller SBM, 1.3% fish meal, 1% wet molasses, and 3.7% vitamins/minerals. Wet corn gluten feed replaced 10% alfalfa hay, 5% corn silage, 5% corn grain, and expeller SBM replaced solvent SBM to maintain diet rumen undegradable protein. The novel product replaced 10% alfalfa hay, 5% corn silage, 3% solvent SBM, and 2% corn. Diet crude protein % and energy density (Mcal/lb, NEL) for control, wet corn gluen feed, and the novel product were 18.4, 0.73; 18.2, 0.75; 18.5, 0.73; respectively. Milk, energy corrected milk, dry matter intake, and production efficiency (ratio of milk to DM intake) did not differ among diets during the first 91 days of lactation, but there was a diet by week interaction for production efficiency. Cows fed control were more efficient during the first 2 weeks postpartum than cows fed wet corn gluten feed and the novel product, likely due to increased fat mobilization from adipose tissue because intake as a percent of body weight was less for cows fed control. During weeks 3 through 14 postpartum, wet corn gluten feed and the novel product improved milk, energy corrected milk, and milk component yield, and production efficiency. Inclusion of wet corn gluten feed and the novel product at 20% of dietary DM as a partial replacement for alfalfa hay, corn silage, corn grain, and SBM in diets fed to lactating dairy cattle supported performance during early lactation and improved performance during mid and late lactation. In addition, combining wet corn gluten feed or the novel product with corn silage and alfalfa hay maintained milk fat yields, thereby demonstrating that they can serve as effective sources of fiber when fed at 20% of dietary DM. Improved performance attributed to wet corn gluten feed and the novel product is due to factors other than improved digestibility of the diets. These results indicate that wet corn gluten feed and the novel product can serve as alternative feedstuffs in diets fed to lactating dairy cattle.
Keywords: Dairy; Wet corn gluten feed; Soybean hulls; Corn steep liquor; By-product